AN ANALYSIS OF SUPPLY CHAIN MANAGEMENT PERFORMANCE OF JENANG RAW MATERIALS IN PONOROGO - ARINDA EMILIA PUTRI; EFFY YUSWITA; FITRIA DINA RIANA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
The success of creating sticky rice jenang is due to a good cooperative relationship between supply chain actors. MSME Jenang Teguh Raharjo faces problems in supply chain performance which then has an impact on the production process, so it is necessary to conduct an assessment of supply chain performance. This study aims to identify the state of supply chain management, analyze the supply chain performance of glutinous rice flour at MSME Jenang Teguh Raharjo using SCOR (Supply Chain Operations Reference) and develop supply chain strategy improvements. This study uses descriptive and quantitative data analysis, carried out at MSME Jenang Teguh Raharjo in February 2021. The respondent determination technique used is non-probability sampling technique and the respondent determination method used is purposive sampling. Data analysis technique with SCOR method. The results showed that there were four members of the glutinous rice flour supply chain. Activities that occur are cooperation to supply the needs of glutinous rice flour as raw material for jenang. Based on the results of the calculation, it can be analyzed that the supply chain performance is not optimal. The average reliability generated is 96% in the Excellent category, the average responsiveness of the three suppliers is in the Good category and the Agility average is 100% in the Excellent category. The recommended repair solution is that suppliers carry out safety stock, Re Order Point, product quality control, production control, make delivery schedules and make improvements to the preparation process.